STUDI PERFORMANSI PENGENDALI SLIDING MODE DAN PID PADA PENGENDALIAN KECEPATAN MOTOR DC - Dian Mursyitah (Situs resmi ITP Press, 2014)
This research was proposed to study the performance of sliding mode and PID controller to control speed of DC motor. Performance study has done by simulation in Matlab/Simulink. Based on observation, the result shows that both of controllers i.e sliding mode control and PID produces good performance. However, based on analysis result, the sliding mode controller produces better performance than PID controller by comparison of transient time is 1 : 3. With the following result are τ = 0.1001 seconds, ts = 0.5005 s, tr = 0.2947 seconds, and td = 0.2487 seconds.